2019
DOI: 10.2147/ndt.s187994
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and outcomes of Guillain-Barr&eacute; syndrome among pediatrics in Saudi Arabia: a 10-year retrospective study</p>

Abstract: Background Guillain-Barré syndrome (GBS) is a progressive acute form of paralysis most probably secondary to an immune-mediated process. GBS among Saudis has been seldom investigated, which leaves both clinicians and researchers with scarcity in knowledge. Therefore, this study aims to assess the prevalence and clinical prognosis of GBS among pediatrics admitted with acute paralysis at a large healthcare facility in Riyadh, Saudi Arabia. Methods This retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 43 publications
4
20
1
Order By: Relevance
“…G uillain-Barré syndrome (GBS) is presently the most common cause of acute flaccid paralysis in our country. Among children in India and neighboring areas, the axonal variety predominates [1][2][3][4][5]; the demyelinating variety predominates in South America [6], other parts of Asia [7][8][9] and Europe [10,11]. This difference in subtypes across geographical areas is not clearly understood [12].…”
mentioning
confidence: 99%
“…G uillain-Barré syndrome (GBS) is presently the most common cause of acute flaccid paralysis in our country. Among children in India and neighboring areas, the axonal variety predominates [1][2][3][4][5]; the demyelinating variety predominates in South America [6], other parts of Asia [7][8][9] and Europe [10,11]. This difference in subtypes across geographical areas is not clearly understood [12].…”
mentioning
confidence: 99%
“…However, Asiri et al 21 who aimed to determine the pattern of muscle weakness in patients with GBS, had results that was not far from the current study. They found that in 80% of patients, muscle weakness started in lower limbs while at presentation four limb weaknesses was the most frequent (96%).…”
Section: Discussionmentioning
confidence: 55%
“…2 Cranial nerves involvement is associated with a shorter time to reach the nadir of illness, 5,11 although cranial facial muscles recover earlier compared with limb muscles. 6 Monolateral facial palsies seem rarer in GBS but definitive conclusions cannot be made due to the limited reports observed. 3,7-9,12-14 A poor prognosis in both pediatric and adult subjects with cranial nerve involvement in the early stage of GBS has been reported 11,15 that seems more severe according to Bhargava et al 5 but without affecting the long-term outcome.…”
Section: Discussionmentioning
confidence: 99%